Atypical migratory reactive arthritis related to Hepatitis C Virus - Clara C. Sánchez-Rodríguez; Ana M. Mendoza-Martínez; Héctor R. Sánchez-Nuncio; Jorge H. Luna-Domínguez (Annals of Hepatology)
Introduction and Objectives: Reactive arthritis (RA) occurs after bacterial infections and is sporadically associated with enterovirus and hepatitis B virus (HBV) and hepatitis C virus (HCV). Clinically, we observe the characteristic triad of arthritis, uveitis and urethritis or diarrhea. We present a patient with RA associated with HCV. Materials and Patients: Fifty-three-year-old man with a history of cannabis use as a youth, suspended 15 years ago. He begins with conjunctival injection, ocular pruritus, increased conjunctival secretion with ocular foreign body sensation, dysuria, and foamy urine. After 24 hours, there was pain, redness, increased volume and significant limitation of the left glenohumeral joint. He received non-steroidal anti-inflammatory drugs (NSAID) with a poor response. Seventy-two hours later, he presented pain in the right coxofemoral joint and 48 hours later in the right knee with increased volume. heat and redness with expansion of the edema to the right lower extremity, highlighting the pain in the ankle, knee and hip joints, which is why he went to the emergency room with suspicion of thrombosis (Image 1). Results: During his hospitalization, a Doppler ultrasound of the lower extremity was performed, ruling out venous thrombosis. The left knee was punctured, obtaining transparent liquid with characteristics of transudate, acellular without bacteria in the biochemical analysis. Serum analysis, general urine analysis, urine culture, VDRL, antibodies against human immunodeficiency virus (HIV), antibodies against hepatitis C virus (Ac vs. HCV), hepatitis B surface antigen (HBVAg) and acute phase reactants (Image 2). Active bacterial infection was excluded, and he received 0.9% saline solution and 150 mg intravenous methylprednisolone every 12 hours, with improvement of symptoms and resolution of uveitis. Active infection with HCV was detected and the patient was discharged with 14 more days on prednisone 10 mg every 24 hours. As an outpatient, he received sofosbuvir/velpatasvir for 12 weeks with sustained viral response at week 12 (SVR12). Conclusions: HCV can induce systemic inflammatory conditions and simulate other infections, such as, in this case, those associated with sexually transmitted bacteria, so it is important to request the Ac vs HCV and, if they are reactive, verify viral replication to administer specific treatment with direct-acting antivirals.